The complete mitochondrial genome of Eastern Yellow Wagtail (Motacilla tschutschensis). Issue 2 (3rd July 2019) - Gao, Xiaodong; Xu, Dajie; Xia, Tian; Dou, Huashan; Sha, Weilai; Zhang, Honghai
Abstract: Motacilla tschutschensis is a species of small passerine bird belonging to the family Motacillidae. Complete mitochondrial genome of Eastern Yellow Wagtail ( M. tschutschensis ) has been sequenced in this study. The genome is 16, 829 bp in length and consists of 13 protein-coding genes, 2 rRNA genes, 1 control region (D-loop), and 22 tRNA genes. The phylogenetic tree was reconstructed using the Bayesian analysis method, indicating that M. tschutschensis was closely related to Motacillalugens and Motacillaalba .